2020
DOI: 10.1515/znb-2019-0146
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of chiral 3,5-bis(l-phenylalaninyl-l-leucinyl)pyridine Schiff base and their macrocyclic carboxaimide derivatives using 3,5-bis(l-phenylalaninyl)-pyridine methyl ester

Abstract: A series of linear tetrapeptides 2-7 and cyclooctapeptedopyridine derivatives 8 and 9, were synthesized using N α -dinicotinoyl-bis[(l-phenylalaninyl-l-leucyl) hydrazide] 2 as starting material. Acid hydrazide 2 was reacted with aromatic or heterocyclic aldehydes to give Schiff base derivatives 3 and 4, respectively. Additionally, compound 2 was reacted with dicarboxylic acid anhydrides ortetracarboxylic diacid anhydrides to give the corresponding linear diimide carboxamides 5-7, and octapeptide tetraimides 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In the present work, some of the prepared tetrapeptide derivatives 3-6 were obtained from N α -dipicolinoyl-bis[(l-phenylalanyl-l-leucine)hydrazide] 2, which was obtained from corresponding ester 1 [39]. Reaction of hydrazide 2 with cycloalkanone derivatives in refluxing glacial acetic acid afforded the corresponding N α -dipicolinoyl-bis[(l-phenylalanyl-l-leucine)-N'-cycloalkylidenehydrazide] 3a-d. Condensation of 2 with active carbonyl derivatives, namely, acetylpyridine or substituted acetophenone derivatives in refluxing acetic acid, gave the corresponding N α -dipicolinoyl-bis[(l-phenylalanyl-l-leucine)-N'-(1-(pyridyl)ethylidene)benzohydrazide] 4a-c and N α -dipicolinoyl-bis-[(l-phenylalanyl-l-leucine)-N'-(1-(substituted phenyl) ethylidene)benzohydrazide] 5a-e, respectively.…”
Section: Chemistrymentioning
confidence: 93%
See 1 more Smart Citation
“…In the present work, some of the prepared tetrapeptide derivatives 3-6 were obtained from N α -dipicolinoyl-bis[(l-phenylalanyl-l-leucine)hydrazide] 2, which was obtained from corresponding ester 1 [39]. Reaction of hydrazide 2 with cycloalkanone derivatives in refluxing glacial acetic acid afforded the corresponding N α -dipicolinoyl-bis[(l-phenylalanyl-l-leucine)-N'-cycloalkylidenehydrazide] 3a-d. Condensation of 2 with active carbonyl derivatives, namely, acetylpyridine or substituted acetophenone derivatives in refluxing acetic acid, gave the corresponding N α -dipicolinoyl-bis[(l-phenylalanyl-l-leucine)-N'-(1-(pyridyl)ethylidene)benzohydrazide] 4a-c and N α -dipicolinoyl-bis-[(l-phenylalanyl-l-leucine)-N'-(1-(substituted phenyl) ethylidene)benzohydrazide] 5a-e, respectively.…”
Section: Chemistrymentioning
confidence: 93%
“…Analytical thin layer chromatography (TLC) was performed on silica gel aluminum sheets, 60 F 254 (E. Merck). Compound 2 was prepared according to our previous reported procedure [39]. N 3 ,N 5 -Bis{1-[(1-(2-cyclooctylidenehydrazinyl)-4-methyl-1-oxopentan-2-yl) N α -dinicotinoyl-bis[L-phenylalaninyl-L-leucyl] Schiff bases 4a-c, 5a-e, and 6a,b.…”
Section: Chemistrymentioning
confidence: 99%
“…Although Tröger base and its analogues have attracted interest of many researcher groups due to their fascinating structures and properties ( Yuan, et al, 2011 ), however, attention has been inadequately focused on these compounds from the biological point of view ( Bailly, et al, 2000 ; Baldeyrou, et al, 2002 ; Manda, et al, 2014 ; Yang, et al, 2015 ). In addition, some of macrocyclic hetero-nitrogen derivatives have been synthesized ( Abu-Ghalia, et al, 2012 ; Amr, et al, 2019 ; Naglah, et al, 2020 ) and have shown promising biological activity, i.e. analgesic and anticonvulsant ( Amr, 2005 ), antimicrobial ( Amr, et al, 2006 ; Azab, et al, 2016 ), anti-proliferative, 5α-reductase inhibiting ( Alanazi, et al, 2020 ), pharmacological ( Al Thagfan, et al, 2018 ), anticancer ( Amr et al, 2018 ), as well as biological activities ( Khayyat and Amr, 2014 ).…”
Section: Introductionmentioning
confidence: 99%